ECO-FASHION: PELATIHAN INOVASI DAN KREATIVITAS PRODUK FASHION DENGAN TEKNIK ECOPRINT - Rahmayani, Dwi; Fauziyah, Izzatul; Runtiningsih, Sri; Tutik; Syahrul Fauzi, Ahmad; Ibnu Tsani, Luthfi (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2025)
Getaspejaten Village boasts a diverse local flora that can be used for industrial purposes by utilizing natural resources to create environmentally friendly products with economic value. This natural potential can be a business opportunity for local villagers. The variety of existing flora, such as leaves, can be utilized to create products with artistic and economic value. These products can be made using the ecoprint technique. Ecoprint is a dyeing technique using natural dyes applied to the fabric's surface. This ecoprint training is expected to enable the community to produce various ecoprint artworks using natural materials such as leaves and flowers in the surrounding environment. The ecoprint training activities are carried out in three stages: preparation, implementation, and completion. Based on this training, ecoprint scarves are produced with unique natural colors and motifs. The Natural Dyes (ZWA) are a mixture of sappanwood and tegeran, with different leaf variations to create unique and aesthetic motifs. Based on interviews, this training activity received more than 90% positive responses from 31 participants. The results of this community service demonstrate that the training has enhanced the community's creativity, knowledge, and skills in processing natural materials into works of art with aesthetic and economic value. Furthermore, effective marketing is expected to increase community income.